Atypical Ischiopagus Conjoined Twins: Discription of a Case - Alanur Güven; Uğur Özkan; Gürkan Kıran; Hakan Kıran (Medical Network, 2006)
Conjoined twinning is extremely rare congenital malformation occurring in a very low frequency. A 22-year-old woman presented with 33 weeks gestation to an obstetric clinic in activ e labor. The patient delivered conjoined male twins vaginally. External examination of the inf ants showed atypical ischiopagus twins. We emphasize that the precise knowledge of anatomic properties of both twins antenatally will help the obstetrician to decide the route of deliv ery and the pediatric surgeon to decide the surgical approach.